A field guide to color a watercolor workbook - Solomon, Lisa (Roost Books, 2019)
"Color is one of the most profound ways we have to express ourselves. In this lively workbook for artists, graphic designers, hobbyists, and creators of all types, you will journal your way through fresh and enriching ways to develop a more personal connection to color in your art and life. Using watercolors, gouache, or any other water-based medium, dive into color theory and explore your personal style while playing with a balanced blend of experiments and color meditations. Discover a personal color wheel while exploring tints and shades. Experiment with color mixing while you make as many of one color as you can – and then name them all (honeydew green, avocado green, mint ice cream…). Through playful prompts and inspiring examples, and with lots of room for painting, this book will guide you to a new or expanded relationship with color and deepen your understanding of what color can do for you."--